COMPARATIVE EVALUATION OF EFFECTIVENESS OF MANAGEMENT OF THE ENTERPRISES OF THERMAL NETWORKS - Evgeniy Beliaev; Iola Kuklite (Вестник Северо-Кавказского федерального университета)
To improve the efficiency of the management of the enterprise of thermal networks it is necessary to objectively compare the management activities of different companies working in different regions and in different conditions to understand the specific situation of the company's energy efficiency management. Existing proposals in this area do not take into account objectively different conditions of operation of enterprises of heating systems. The studies of several enterprises of heating systems over the period 2011-2015. The proposed measure for comparing the eficiency of management of the enterprises of thermal networks in the ield of energy efficiency, working in different conditions - the coefficient of efficiency of management. The proposed method and calculation formulas for determining this factor.